Analisis Penerapan Etika Bisnis Islam Dan Pembiayaan Mikro Syariah Dalam Mendukung Perkembangan UMKM - Syahfitri, Mulia; Jannah, Nurul; Syahriza, Rahmi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study aims to examine the application of Islamic business ethics and the utilization of Islamic microfinance in fostering the development of bakso (meatball) micro, small, and medium enterprises (MSMEs) in Deli Tua District. Adopting a descriptive qualitative approach, data were collected through observation and semi-structured interviews with six bakso shop owners selected via purposive sampling. The data were analyzed using the Miles and Huberman framework, encompassing data reduction, data display, and conclusion drawing. The findings reveal that the implementation of Islamic business ethics—particularly honesty and social responsibility—significantly enhances customer loyalty and strengthens business image. Furthermore, Islamic microfinance based on murabahah contracts contributes to increasing production capacity and improving business facilities. The synergy between ethical practices and Islamic financing not only reinforces business reputation but also facilitates access to Sharia-compliant funding. The study suggests that integrating ethical values with Islamic financial mechanisms can serve as an effective strategy for promoting sustainable MSME growth